Gadamer on Historicity and Philosophy A critical Examination - Wolsing, Peter (Res Cogitans, 2020)
The aim of this paper is to substantiate the view that historicity (Geschichtlichkeit) which is an epistemological presupposition of Gadamer’s idea of ‘concept history’ (Begriffsgeschichte) violates the substance of philosophy considerably, i.e. its problems and conceptuality, because of the limits it sets to the reach of thoughtful consideration (Denken). I argue that if philosophy shall be possible as an epistemic activity intended for knowledge, a theory which defends the universality of thinking must be added to Gadamer’s hermeneutics. This paper shows how his theory unjustly ignores ‘thoughtful consideration’ as a primordial phenomenon of consciousness which is present on higher levels of understanding. After the criticism of Gadamer’s inadequate concept of knowledge the paper concludes with a suggestion to rehabilitate the classical notion of thoughtful consideration as the substantive and permanent presupposition of all philosophy. The paper demonstrates how the rise of knowledge from Verstehen to Denken on different levels of reflection must lead to a rehabilitation of the philosophy of subjectivity and of metaphysics and how this epistemological move must affect the idea of a ‘destruction of metaphysics’ which Gadamer shares with Heidegger.